Types of Rest According to the Labor Legislation Applied by the Employees of the National Police of Ukraine - O. V. Veklіyk (Bulletin of Kharkiv National University of Internal Affairs)
The author has researched one of the directions of the modern formation and development of the rule of law state related to the improvement of various branches of law and the relevant legislation in the field of labor law.